(untitled) - Katz, Arthur; (1929-2007) (U.S.A, 1999)
In his penetrating manner, the author seeks to capture the flavor and essential meaning of this most holy foundation. Few have adequately understood that unless the Church is built on this foundation, then it simply is not the Church in any authentic way.
Keywords: Christian life